Northern Hemisphere Extratropical 2000-Year and 500-Year Temperature Reconstructions - Christiansen, Bo; Charpentier Ljungquist, Fredrik (Danish Meteorological Institute, 2019)
We present two new multi-proxy reconstructions of the extra-tropical Northern Hemisphere (30-90°N) mean temperature: a two-millennia long reconstruction reaching back to 1 AD and a 500-yr long reconstruction reaching back to 1500 AD. The reconstructions are based on compilations of 32 and 91 proxies, respectively, of which only little more than half pass a screening procedure and are included in the actual reconstructions. The proxies are of different types and of different resolutions (annual, annual-to-decadal, and decadal) but all have previously been shown to relate to local or regional temperature. We use a reconstruction method, LOCal (LOC), that recently has been shown to confidently reproduce low-frequency variability. Confidence intervals are obtained by an ensemble pseudo-proxy method that both estimates the variance and the bias of the reconstructions. The two-millennia long reconstruction shows a well defined Medieval Warm Period, with a peak warming ca. 950-1050AD reaching 0.6°C relative to the reference period 1880-1960 AD. The 500-yr long reconstruction confirms previous results obtained with the LOC method applied to a smaller proxy compilation; in particular it shows the Little Ice Age cumulating in 1580-1720AD with a temperature minimum of -1.0°C below the reference period. The reconstructed local temperatures, the magnitude of which are subject to wide confidence intervals, show a rather geographically homogeneous Little Ice Age, while more geographical inhomogeneities are found for the Medieval Warm Period. Reconstructions based on different subsets of proxies show only small differences, suggesting that LOC reconstructs 50-yr smoothed extra-tropical NH mean temperatures well and that low-frequency noise in the proxies is a relatively small problem.

The dataset can be downloaded from:
https://www.ncei.noaa.gov/access/paleo-search/study/12902

Två nya multi-proxy-rekonstruktioner av den extra-tropiska norra halvklotet (30-90 ° N)

För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/ecds0083

Datasatsen kan laddas ner från:
https://www.ncei.noaa.gov/access/paleo-search/study/12902
2000 års och 500-års temperaturrekonstruktioner för den extratropiska norra halvklotet
Keywords: COMMON SENSE CLIMATE INDEX; AIR TEMPERATURE RECONSTRUCTION; CLIMATE INDICATORS; Natural Sciences; Naturvetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi